PENERAPAN MODEL STAD (STUDENT TEAMS ACHIEVEMENT DIVITION) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X MA ZAINUL MUSTHAFA NW PENGADANG TAHUN PELAJARAN 2012/2013 - Mirnawati Mirnawati (Universitas Pendidikan Mandalika, 2013)
Mastery of physics concepts of students including low category and application of learning model has not varied, still refers to the old paradigm such as teaching by lecture method. This study aims to determine the application of STAD model (Student Teams Achievement Division) to improve student learning outcomes of grade X MA Zainul Musthafa NW Pengadang academic year 2012/2013. This research is a classroom action research conducted in 2 cycles consisting of planning, implementation, observation, evaluation and reflection. The first cycle consists of three sessions and the second cycle is two sessions. Data on student learning outcomes is obtained from multiple choice tests at the end of the cycle. The results showed that the completeness of classical learning in the first cycle was 64.00% and 91.67% for the second cycle. We conclude that the application of the STAD model has a positive impact on student learning outcomes.